ALAVAR SHAHAR KI NAGARIY AKARIKI ANTARIK BHUGOL VA UNKE VIBHINNA KARYO ME UPAYOG KA ADHAYAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2020)
ALAVAR SHAHAR KI NAGARIY AKARIKI ANTARIK BHUGOL VA UNKE VIBHINNA KARYO ME UPAYOG KA ADHAYAN